2015
DOI: 10.1093/ntr/ntu263
|View full text |Cite|
|
Sign up to set email alerts
|

Black Cigarette Smokers Report More Attention to Smoking Cues Than White Smokers: Implications for Smoking Cessation

Abstract: Introduction: Black cigarette smokers have lower rates of smoking cessation compared with Whites. However, the mechanisms underlying these differences are not clear. Many Blacks live in communities saturated by tobacco advertisements. These cue-rich environments may undermine cessation attempts by provoking smoking. Moreover, attentional bias to smoking cues (attention capture by smoking cues) has been linked to lower cessation outcomes. Cessation attempts among Blacks may be compromised by attentional bias to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Self-reported attentional bias was assessed with the Subjective Attentional Bias Questionnaire (SABQ), an eight-item questionnaire that assesses the extent to which participants notice that their attention is captured by cigarettes and smoking cues (Leventhal et al, 2007;Robinson et al, 2015). In the current sample, Cronbach’s alpha for the SABQ was: visit 1) α = .90; visit 2) α = .88; and visit 3) α =.91.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-reported attentional bias was assessed with the Subjective Attentional Bias Questionnaire (SABQ), an eight-item questionnaire that assesses the extent to which participants notice that their attention is captured by cigarettes and smoking cues (Leventhal et al, 2007;Robinson et al, 2015). In the current sample, Cronbach’s alpha for the SABQ was: visit 1) α = .90; visit 2) α = .88; and visit 3) α =.91.…”
Section: Methodsmentioning
confidence: 99%
“…abstinent vs. smoking conditions). In study 2, the between race difference in smoking cessation was partially mediated by self-reported attentional bias (Robinson et al, 2015). There is also evidence that African Americans have enhanced brain activation compared to Whites in response to smoking vs. neutral cues in the medial prefrontal cortex, and right lateral orbitofrontal cortex (Okuyemi et al, 2006).…”
mentioning
confidence: 99%
“…The final four papers in this themed issue focus on intervention issues of relevance to specific ethnic groups in the United States and as well as at-risk populations abroad. First, Robinson and colleagues 22 describe results from two US studies that suggest that black smokers report attending more to smoking cues than white smokers. Results provide support for a potential mechanism underlying tobacco-related health disparities among black smokers, who tend to reside in cue rich environments.…”
mentioning
confidence: 99%
“…46 À .89). Other studies have demonstrated different estimates of internal reliability (Robinson et al 2015;Spanakis et al 2019), however most do not report reliability despite its integral role in effect estimates and reproducibility (Baugh 2002).…”
Section: Introductionmentioning
confidence: 97%